HASIL BELAJAR KOGNITIF SISWA MELALUI IMPLEMENTASI MEDIA PEMBELAJARAN TEORI KINETIK GAS BERBASIS PENDEKATAN INKUIRI DI KELAS XI MIA 3 SMA NEGERI 4 PEKANBARU - Clara Tarania Pramudya; Zulhelmi Zulhelmi; M.Nor M.Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study is to find the result of student’s cognitive through the implementation of gas kinetic learning media based on inquiry approach of XI MIA 3 SMAN 4 Pekanbaru.This research form is pre experimental with oneshot case study methode. The data of this study is student’s cognitive score by post test. The analysis conducted on the student’s cognitive learning outcomes in the form of study absorpstion, learning efectivity and the percentage of student’s pass of each tested indicator. The result obtained from this study are, from 36 students, 3 student have a very good study absorption, 23 have a good study absorption, 8 have a well study absorption, 1 have a less good study absorption and 1 fail. The learning efectivity is on good category with percentage of 69,4%. The conclusion is physics learning with inquiry approach goes well.Keywords : Inquiry approach, cognitive study result